Soyghurt Supernatant on Mouse Embryonic Fibroblast (MEF) Cell - Lantika, Uci Ary; Khairani, Astrid Feinisa (Universitas Islam Bandung, 2019)
Yogurt is a functional food developed with various modifications in the fermentation process. Replacing animal milk into soymilk as raw material is one approach. Yogurt has a good effect on human health. Probiotic and bioactive compounds in yogurt can inhibit cell proliferation and stimulate apoptosis on the cancer cell line. However, there is no report about the effect of yogurt on a normal cell. This research was conducted to examine the impact of soyghurt supernatant intervention toward the viability of mouse embryonic fibroblast (MEF) cell. The is an in vitro study using MEF cell isolated from 10th days gestational age mice embryo conducted at Microbiology Laboratorium and Cell Culture and Cytogenetic Laboratory, Universitas Padjadjaran, Bandung in November 2018–January 2019. Soyghurt made from soymilk fermented by Lactobacillus bulgaricus ATCC 11842. The number of the bacterial colony calculated by total plate count (TPC) method and pH calculated by pH meter. Soyghurt supernatant was made from soyghurt and then intervened into MEF cells by 1–20% concentration. The cell viability showed in the 50% inhibitory concentration (IC50) analysis. The intervention of soyghurt supernatant at 1–20% concentration showed there was no proliferation inhibition until 50% population (IC50). However, from the morphology analysis, there was MEF cell morphology alteration on the group given soyghurt supernatant with >12.5% concentration. Counter mechanism effect from soymilk fermentation by probiotic could be the driver for this result. In conclusion, soyghurt supernatant intervention at 1–20% concentration did not have a cytotoxic effect on MEF cell, but enhancement of soyghurt supernatant concentration can increase cytotoxic potential. SUPERNATAN SOYGHURT PADA SEL MOUSE EMBRYONIC FIBROBLAST (MEF)Yoghurt merupakan functional food yang dikembangkan dengan berbagai modifikasi dalam proses pembuatannya. Mengganti susu hewan dengan susu kedelai sebagai bahan baku adalah salah satunya. Yoghurt memiliki efek yang baik bagi kesehatan manusia. Senyawa probiotik dan bioaktif pada yoghurt dapat menginhibisi proliferasi sel dan menstimulasi apoptosis pada sel lini kanker. Akan tetapi, tidak terdapat laporan mengenai efek yoghurt pada sel normal. Penelitian ini dilakukan untuk menguji pengaruh intervensi supernatan soyghurt terhadap viabilitas sel mouse embryonic fibroblast (MEF). Ini adalah penelitian in vitro menggunakan sel MEF yang diisolasi dari embrio tikus hari ke-10 usia kebuntingan yang dilakukan di Laboratorium Mikrobiologi dan Laboratorium Kultur Sel dan Sitogenetika, Universitas Padjadjaran, Bandung pada November 2018–Januari 2019. Soyghurt dibuat dari susu kedelai yang difermentasi oleh Lactobacillus bulgaricus ATCC 11842. Jumlah koloni bakteri dihitung dengan metode total plate count (TPC) dan pH diukur dengan pH meter. Supernatan soyghurt dibuat dari soyghurt dan kemudian diintervensi ke dalam sel MEF dengan konsentrasi 1–20%. Viabilitas sel ditunjukkan dalam analisis penghambatan 50% (IC50). Pemberian supernatan soyghurt konsentrasi 1–20% menunjukkan tidak terdapat inhibisi proliferasi 50% (IC50). Namun, dari analisis morfologi, terdapat perubahan morfologi sel MEF pada kelompok yang diberi supernatan soyghurt dengan konsentrasi >12,5%. Efek mekanisme yang saling meniadakan dari fermentasi susu kedelai dengan probiotik diduga menjadi mekanisme hasil dari penelitian ini. Simpulan, intervensi supernatan soyghurt pada konsentrasi 1–20% tidak memiliki efek sitotoksik pada sel MEF, namun peningkatan konsentrasi supernatan soyghurt dapat meningkatkan potensi sitotoksik.